Fungsi ekonomi kota kecamatan dalam pembangunan wilayah: Studi kasus Kabupaten Sukoharjo - Nurhadi, Bayu (Nur Science Institute, 2021)
The sub-district has complete government and vertical agency apparatus as the lowest administrative unit. It has access to the bottom, which is very suitable to be developed as a service center and a center for developing rural areas. Thus the development and economic growth of the region are influenced by the function of the sub-district city. The problems faced in development in Sukoharjo district include the availability of socio-economic facilities and infrastructure at the sub-district level, The function of the sub-district city in regional economic development, and the system and the role of markets in the development of the selected sub-district area. Qualitative analysis was used to analyze the profile and role of the market in the economic development of the sub-district area, the role of the market, and the service area of the sample market. Meanwhile, quantitative analysis was conducted to analyze the relationship between regional resources and the availability of socio-economic facilities. Based on the scalogram analysis, parallel overlap analysis, Linkert scale, and also the Spearman correlation test, it can be concluded that there is a relationship between resource potential and the availability of socio-economic facilities, and there is also a reciprocal relationship between accessibility and the economy as well as a reciprocal relationship between the magnitude of market activity and community economic activities in the sub-region